Measuring the Role of Reductive Bias in Social Enterprise Formation: Development and Validation of a Social Entrepreneurial Intention Bias Scale. Issue 2 (4th May 2022) - Chipeta, Eleanor Meda; Venter, Robert; Kruse, Philipp
Abstract: Social entrepreneurship (SE) has become a global phenomenon that is increasingly receiving institutional support as a business model designed to address social problems. However, despite having a global presence, enthusiasm for SE has run ahead of its scientific enquiry. As the field is still developing, the empirical nature of SE research has become a major cause for concern. Consequently, the target for this current study was twofold: Firstly, to propose and validate a scale to measure social entrepreneurial intention bias (SEI-Bias) using a German and a South African sample of university students ( N total =595). Secondly, to identify patterns of social entrepreneurial antecedents among people with a high SEI-Bias compared to people with a low SEI-Bias. Applying exploratory and confirmatory factor analyses, and correlation analysis, to develop and validate a robust SE intention bias scale comprising of three Reductive Bias (RB)-facets. Furthermore, based on a rather low or high level of each of the three RB-facets, significant differences were found in the level to which RB influences SE intention. Additionally, an outline of the implications and limitations of our findings as well as recommendations for future practice were made.